Hepatoprotective Effects of Milkfish (Chanos chanos) Oil and Silymarin Against Isoniazid–Rifampicin-Induced Liver Injury in Rats - Heru Sasongko; Mikael Hovhanness; Arinda Handiyah Sawitri; Aulia Hanundita Maharani; Delia Putri Hedianti; Josua Arianto Hutasoit; Lathyfa Asyraq; Listiyana Ika Safitri; Lois Elda Zai; Sutarno Sutarno (Faculty of Pharmacy, Universitas Gadjah Mada, 2026)
The objectives of the present research were to assess the hepatoprotective activities of milkfish oil (MFO) and silymarin (SL) against rifampicin (RFP) and isoniazid (INH) induced hepatotoxicity. Rats were divided into seven groups: normal control, negative control (INH+RFP), silymarin alone (50 mg/kg BW/day), low-dose MFO (MFO-L), high-dose MFO (MFO-H), low-dose combination (SL+MFO-L), and high-dose combination (SL+MFO-H). Rats receiving RFP and INH showed raised liver enzymes and typical signs of hepatotoxicity. Analyzed parameters comprised proinflammatory mediators (tumor necrosis factor-alpha and interleukin-6), antioxidant markers (catalase, glutathione, malondialdehyde, and superoxide dismutase), cytochrome P450, total protein, aspartate aminotransferase (AST), alanine aminotransferase (ALT), albumin and bilirubin. Treatment with a combination of MFO plus SL remarkably decreased hepatic enzyme activities, oxidative stress and inflammation, and suggested a prevention effect against the drug-induce liver injury.